x = 1
x = -1
y = 1
y = -1
x + y = 1
Correct answer is C
The linear equation will be the difference between the equation.
y=x2 + 4x - 6 and x2 + 4x - 7 = 0
y=x2 + 4x - 6, ( 0 = x2 + 4x - 7)
y = -(-1) y = 1
If log 10 to base 8 = X, evaluate log 5 to base 8 in terms of X. ...
A man earns N3,500 per month out of which he spends 15% on his children's education. If he spend...
The graph of the quadratic expression ...
In how many ways can the word MACICITA be arranged?...
The identity element with respect to the multiplication shown in the diagram below is \(\begin{...
Find the positive number n, such that thrice its square is equal to twelve times the number ...